Characterization of the chloroplast genome of Symbiochlorum hainanensis (Ulvophyceae, Chlorophyta) and its phylogenetic analysis - Fangfang Yang; Yi Huang; Lijuan Long (Mitochondrial DNA. Part B. Resources, 2023)
Symbiochlorum hainandiae S.Q. Gong & Z.Y. Li, 2018 is a unicellular green alga belonging to Ulvophyceae, Chlorophyta, and plays important roles in coral reef ecosystem. In this study, high-throughput sequencing technology is used to sequence and assemble the chloroplast genome of S. hainandiae. The complete chloroplast genome of S. hainandiae was 158, 96 bp with the GC content of 32.86%. A total of 126 genes were identified, including 98 protein-coding genes, 26 tRNA, and 2 rRNA genes. The inverted repeat region was lost in the complete chloroplast genome of S. hainandiae. The phylogenetic analysis supports that S. hainandiae is a new sister lineage to the genus Ignatius within the class Ulvophyceae.